14.6k views
0 votes
- 4x - y = 4
y = 2x + 2

User Jianing
by
7.5k points

2 Answers

1 vote

Answer:

Solution: (1,4)

Explanation:

- 4x - y = 4

y = 2x + 2

We can use substitution

- 4x - 2x + 2 = 4

combine like terms

- 2x + 2 = 4

subtraction property of equality

- 2x + 2 - 2 = 4 - 2

-2x = 2

division property of equality

(-2x)/-2x = 2/2

x = 1

Now you can plug in the value of x into the second equation to find y

y = 2x + 2

y = 2(1) + 2

y= 2 + 2

y = 4

Solution: (1,4)

User Luan
by
6.8k points
5 votes

Answer:

Explanation:

- 4x - y = 4 y = 2x + 2-example-1
User Chris Tierney
by
7.0k points